Exploring disaster preparedness in an obstetric unit in a district hospital in the Western Cape Province - Carla Horn; Nokwanda Edith Bam; Molekodi Jacob Matsipane (BMC, 2024)
Abstract Background Research on disaster preparedness in public hospitals is limited, and specialised units such as obstetric departments need to be even more prepared when rendering health care to vulnerable populations. Disasters can be natural, such as floods due to human interventions, sinkholes due to mining, or pandemic occurrences, such as the recent COVID-19 pandemic. Research on disaster preparedness is limited, and even more so in specialised units such as obstetrics and evacuating a ward of maternal and neonatal patients present unique challenges. Being prepared for any disaster is the only assurance of effective patient healthcare during a disaster. This study explored and described nurses' knowledge and attitudes regarding preparedness for a disaster in an obstetric unit in a public institution. The study aimed to make recommendations to improve disaster preparedness in an obstetric ward based on the nurses' knowledge and attitudes. Methods This study utilised an exploratory, descriptive qualitative design within a contextual approach. The data were acquired through individual interviews that were done using a semi-structured interview schedule. An observational walkabout was performed with the unit manager to validate interviewee responses. The study employed purposive sampling with a sample size of 17 nurses (N = 32, n = 17) and a response rate of 53%. The interviews were transcribed verbatim, and later, the data underwent analysis using theme analysis and a co-coder. Results The results indicate that the participants demonstrate an awareness of disaster terminology but need more assertiveness in executing the institutional disaster policy. The results illustrate that more frequent training, disaster rehearsals, and simulations should be implemented to improve disaster readiness. Strategies are recommended to enhance preparedness for a disaster in the obstetric unit. Conclusion The study findings recommend more education and training opportunities that should be regularly instilled as a practice within the obstetric ward. More disaster drills and simulation exercises should be performed to ensure confidence in disaster preparedness. Obstetric staff of all levels should be involved with policymaking and disaster plan development.